Prevalence, severity, and risk factors of work-related musculoskeletal disorders (WMSD) among stevedores in a break-bulk port terminal - Sedilla, Keneth B.; Matias, Aura C. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
The Philippines is primarily linked to the international trade system through maritime transportation sector. The country's archipelagic configuration requires a network of various seaport terminals which enables an efficient and cost-effective flow of goods and commodities across different geographical locations. While it plays a vital role in the country's economic developments, port operations host a wide spectrum of health problems and work-related diseases. The International Labour Organization (ILO) estimates that of the total 2.34 million work-related deaths per year, 86% are due to work-related diseases which include musculoskeletal disorders. Based on the nature of work in port terminals, workers involved in vessel loading and unloading operations specifically for break-bulk cargoes carry out a set of tasks which, if not properly managed, may result to a variety of work-related musculoskeletal disorders (WMSD). Thus, this study is intended to establish a baseline data on work-related musculoskeletal disorders on stevedoring operations in break-bulk port terminals through an ergonomic assessment. This study aims to address the problem on or investigate the prevalence, severity and risk factors that contribute to the occurrence of work-related musculoskeletal disorders among stevedores, and come up with ergonomic measures to minimize their exposure to significant risk factors. In this cross-sectional study, self-administered questionnaires with self-reported symptoms were used in conducting the surveillance for the work-related musculoskeletal disorders among the stevedores. Overall, the results of the study has shown that WMSDs are reasonably prevalent particularly in stevedores' upper extremities. Prevalence of self-reported symptoms for musculoskeletal disorders was highest for the shoulders (64.48%), forearm (62.07%), upper back (60.34%), and lower back region (58.28%). The significant risk factors associated with the severity level of work-related musculoskeletal symptoms were obtained using ordinal logistic regression. Moreover, Spearman's correlation and chi-squared attribute evaluation were utilized for the correlation analysis. A wide variety of WMSD risk factors were identified from the regression models suggesting that the etiology of this condition is both complex and multifaceted. Ordinal logistic regression models for the body regions with high prevalence rates revealed a number of remarkable relationships between severity level of work-related musculoskeletal disorders and individual/work-related factors. Among the individual risk factors, 'age', 'years of work experience in the break-bulk port terminal', 'cigarette smoking', and 'alcoholic drinks consumption' were identified as significant risk factors. Furthermore, 'vessel work assignment', 'type of steel commodity', 'average number of days of work per week', 'job satisfaction', and 'job security' are the significant predictors amongst the work-related factors. Finally, based on the results of the study, specifically on the significant factors identified, ergonomic measures such as engineering and administrative controls were developed to reduce stevedores' risks exposure.
Thesis (M.S. Industrial Engineering)--University of the Philippines Diliman
Keywords: Stevedores; Musculoskeletal system -- Diseases